Observation of Top Quark Production in Proton-Nucleus Collisions - Sirunyan,AM; Turnasyan,A; Adam,W; Arribrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Del,Valle AE; Flechl,M; et al. (Physical Review Letters, 2017)
The first observation of top quark production in proton-nucleus collisions is reported using proton-leaddata collected by the CMS experiment at the CERN LHC at a nucleon-nucleon center-of-mass energy of ffiffiffiffiffiffiffiffisNN p ¼ 8.16 TeV. The measurement is performed using events with exactly one isolated electron or muoncandidate and at least four jets. The data sample corresponds to an integrated luminosity of 174 nb−1.The significance of the t¯t signal against the background-only hypothesis is above 5 standard deviations.The measured cross section is σt¯t ¼ 45 8 nb, consistent with predictions from perturbative quantumchromodynamics.